Elevational filtering and the evolution of planthoppers (Hemiptera, Fulgoromorpha) in Papua New Guinea. (19th October 2019) - Chatelain, Paul; Le Cesne, Maxime; Elias, Marianne; Guilbert, Eric; Soulier‐Perkins, Adeline
Abstract: Along elevational gradients, phylogenetic relatedness patterns constitute a considerable source of information and may shed light on ecological processes that structure communities. This study focuses on community phylogenetic structure of planthoppers, specifically the species‐rich and abundant Fulgoromorpha families (Hemiptera, Auchenorrhyncha), Cixiidae and Derbidae + Achilidae, along an elevational gradient on Mount Wilhelm (Papua New Guinea). In order to assess the factors driving planthoppers community composition, we recorded abundance data for planthoppers species at each elevation and we generated a molecular phylogeny of the local species, using Bayesian inference. We analyzed 168 individuals representing 59 local morphospecies. Using a fully resolved and well‐supported phylogeny, we then investigated the phylogenetic structure of the communities by performing a Spatial Analysis of Community Diversity. We show that Cixiidae are phylogenetically clustered along the elevational gradient, whereas Derbidae + Achilidae harbor a random structure, suggesting that local adaptation to elevation shapes community structure of Cixiidae, but not that of Derbidae + Achilidae. Our findings highlight the importance of phylogenies in the study of tropical elevational gradients.